Status and Safety Signals of Cephalosporins in Children: A Spontaneous Reporting Database Study - Cai, Yuanxuan; Yang, Linhui; Shangguan, Xiaofang; Zhao, Yuhang; Huang, Rui (Frontiers in Pharmacology, 2021)
Introduction: Cephalosporins are widely used in clinical treatment of children, but it is difficult to carry out clinical trials and there is no strong evidence of their safety. Therefore, adverse drug reactions (ADR) of cephalosporins can be a public health problem that deserves attention. Methods: ADR reports collected by the Hubei Adverse Drug Reaction Monitoring Center from 2014 to 2019 were analysed. The safety of Cephalosporins was described by descriptive analysis and three signal mining methods, including the reporting odd ratio (ROR), proportional reporting ratio (PRR) and comprehensive standard method (MHRA). Results: The findings indicated that the age groups of 0-1 and 2-3 years had the highest rates of reporting ADRs. Children aged 0-4 years reported more ADRs, while the proportion of severe ADRs was lower than the average (6.63%). Among the 37 cephalosporins, the severe ADRs of ceftezole, ceftazidime, cefoperazone/sulbactam, cefotaxime, ceftriaxone were reported more and the proportion of severe ADRs was higher. The proportion of severe ADRs of most cephalosporin compound preparations was higher than that of corresponding single components. A total of 99.18% of the cases improved after treatment. There were 4 deaths whose ADRs were mainly anaphylactic shock, dyspnoea and anaphylactoid reaction. In signal mining, the three methods produced 206 signals that were the same, and 73 of them were off-label ADRs. Conclusion: ADRs were common but not serious in children aged 0-4 years. And the reported rate of serious ADRs in children aged over 4 years increased with age. ADR reports of ceftezole, ceftazidime, cefoperazone/sulbactam, cefotaxime, ceftriaxone were numerous and serious, and the safety of cephalosporin compound preparations in children was doubtful. Ceftezole may cause off-label ADRs including tremor, face oedema, cyanosis, pallor, rigors and palpitation. The labeling of ADRs in children in cephalosporin instructions and the record of allergic history need to be improved.